Globalization and Federation in Peril: Renewed Agitations for Statehood and the Future of Nigerian State - A. M. Maigari; U. Dantani (Glocalism: Journal of Culture, Politics and Innovation)
The paper examines how globalization induces tensions and prejudices in the federal state of Nigeria, which lead to separatist and secessionist movements. The methodological issues are based on documentary and content analyses and adopt a sociological approach as the framework of analysis. The approach argues that a federal structure permeated by forces of globalization, primordial sentiments and pretensions, agitations for self-determination are presented as separatist or secessionist movements. Research finding argues that the onset of globalization in Third World nations was perpetuated through colonial domination which created a divide and rule policy in the federal state of Nigeria. The policy of domination and marginalization by European colonialist and continued by the first republic politicians and military dictators have triggered agitations and counter agitations for secessionism in Nigeria. It is also argued from the research finding that deregulation of the downstream sector of the Nigerian oil industries in the Niger Delta region, one of the forces of globalization creates and intensifies unemployment, brings abject poverty and hunger, looses soil fertility, creates environmental pollution and degradation, destroys aquatic animals and prevalence of oil spillage. The outcome was the intensification of militancy operations in the region-fuelled secessionist movement by the inhabitants of oil producing communities. Furthermore, it is indicated by the finding of the research that trade liberalization – a rule of the game of globalization – allows the intrusion of small arms and light weapons into Nigeria by the secessionist movements and Boko Haram insurgents who want to establish an Islamic state based on theocracy. Possession of logistics and their applications for secessionism, therefore, pose a serious challenge to the corporate existence federalism in Nigeria. Moreover, the contagious theory effect of globalized media that provides chances of spreading the philosophy and successes of other secessionist movements elsewhere into the federal structure of the country has aided the process of agitations for separatism. The paper concludes that despite the demands for secessionism, the process left much to be desired as the Nigerian state continues to exist under a unified and indivisible country.